AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DALAM UPAYA MENINGKATKAN PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT - Nafidah, Lina Nasihatun; Suryaningtyas, Mawar (BISNIS, 2015)
This research focuses attention on accountability in the management of Village Funds Allocation (ADD) in efforts to improve the development of the village and community empowerment. This research is expected to be useful in efforts to improve the accountability of the management of Village Funds Allocation. The results of this research showed that the accountability ADD both technically and administration has een running well in accordance with the applicable rules with evidence of accountability in a transparent and accountable, so also in the management of village funds allocation, proven by the existence of Accountability Report (LPJ) the contents of which there is a cash book receipt, aiding, news events and other activities that have been documented through the pictures that are attached and physical development has been carried out the construction by constructing the irrigation water stones times. The realization of the report and report the realization of the implementation of Regional Budget Villages communicated to the society in writing and with the media information that is easily accessible by the community as shown by the existence of an attachment realization of that has been written. The planning, implementation, accountability for the development and empowerment of the village Dapurkejambon also has been done by the government of the village in accordance with the existing regulations, proven by the existence of the stages of planning activities can be done preparation in the form of the arrangement of the list of the Proposed Planned Activities (DURK) and Business Plan and Budget (RKA) that activities financed by the Fund Allocation of the village. However the purpose of the Fund Allocation Village in increasing community empowerment Dapurkejambon still deemed less than optimal because of the community less respond with good.